Event-based prospective memory in patients with Parkinson’s disease: the effect of emotional valence - Mioni, G.; Meligrana, L.; Rendell, P. G.; Bartolomei, L.; Perini, F.; Stablum, F. (Frontiers in Human Neuroscience, 2015)
The present study investigated the effect of Parkinson’s disease (PD) on prospective memory (PM) tasks by varying the emotional content of the PM actions. Twenty-one older adults with PD and 25 healthy older adults took part in the present study. Participants performed three virtual days in the Virtual Week task. On each virtual day, participants performed actions with positive, negative or neutral content. Immediately following each virtual day, participants completed a recognition task to assess their retrospective memory for the various prospective memory tasks. PD patients were less accurate than the control group at both PM accuracy and recognition task accuracy. The effect of emotional valence was also evident, indicating that all participants were more accurate on positive PM tasks than both negative and neutral. This study confirmed PM impairment in PD patients and extended previous research showing how positive emotional stimuli can influence PM performance.